Penerapan Squid sebagai Filtering Web dan Manajemen Bandwidth pada Jaringan Internet - Irwanda, A’af Teguh; Khairil, Khairil; Sapri, Sapri (LPPM UNIKA Santo Thomas Medan, 2023)
The application of Squid as web filtering and bandwidth management on the Internet Network at SMK Negeri 1 Kepahiang was built using the Linux Ubuntu Server 20.04.5 operating system. Web filtering is used to block several websites including youtube.com, facebook.com, and instragram.com. Besides that, bandwidth management is carried out, so that internet access is divided evenly, where there are 3 parts, namely teachers, staff and students.Based on the tests that have been carried out, it can be concluded that the application of Squid can help filter websites so that the teaching and learning process is not disrupted and administrative management can be carried out without any interruptions, and can regulate bandwidth on the internet network so that it is evenly distributed both downloads and uploads